2019
DOI: 10.21303/2504-5695.2019.00849
|View full text |Cite
|
Sign up to set email alerts
|

Research of Consumer Properties of Developed Biscuits Based on Organic Raw Materials

Abstract: The article discusses the recipes of new biscuits based on organic raw materials, as well as the results of the study of their quality and safety indicators. The aim of this research is studying the consumer properties of biscuits, developed on the basis of organic raw materials, which will expand the range of organic confectionery products. The main difference between the developed biscuit recipes is that instead of wheat flour buckwheat flour, spelled flour and hemp flour were used, and coconut and maple sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The data in Table 3 indicate that the content of toxic elements in organic cookies is lower than set by regulatory requirements. Studies [6][7][8] also found a lower content of heavy metal salts in products made from organic raw materials. Thus, we can conclude about the effectiveness of the use of organic raw materials to improve the safety of finished products.…”
Section: Discussion Of Results Of Studying the Devised Organic Cookiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The data in Table 3 indicate that the content of toxic elements in organic cookies is lower than set by regulatory requirements. Studies [6][7][8] also found a lower content of heavy metal salts in products made from organic raw materials. Thus, we can conclude about the effectiveness of the use of organic raw materials to improve the safety of finished products.…”
Section: Discussion Of Results Of Studying the Devised Organic Cookiesmentioning
confidence: 95%
“…Despite a significant body of research into the biological value of organic agricultural produce, the range of organic flour products is still not wide enough. There are data regarding the development of new recipes for muffins [6], cookies [7], cakes [8], waffles [9] based on organic raw materials. The above studies prove that flour products developed from organic raw materials have high consumer properties.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Its fruits, leaves and the bark of shoots as a valuable vitamins and energy, adaptogenic product in the market of many countries of the world, is very popular and the purchase price, which determines the laying of industrial plantations (Pantielieieva, 2006;Skalski et al, 2018;. The most common fruit processing products are sea buckthorn oil, cider, wine, jelly, sauces, jams, marmalade, juices -not replaceable components of healthy eating (Litovchenko & Kuznetsov, 2019;Tkachenko et al, 2019). It's worth noting that plantations of sea buckthorn play an important role as forest ameliorants, protecting the soil from wind and water erosion (Bobyliov et al, 2014;Grynyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Current trends in the formation of a healthy diet dictate the need to create new products with increased biological and physiological value (Sіzaуа et al, 2017;Kozlowska et al, 2018;Zakłos-Szyda et al, 2019). In order to preserve the environment more and more attention is being paid to organic production of agricultural products (Živělová & Crhová, 2013;Boyko et al, 2016;Bryła, 2016;Boyko & Brygadyrenko, 2017;Tkachenko et al, 2019). This is the guarantor of obtaining regulatory safe raw materials and food, the recipes of which include no synthetic preservatives, fragrances, dyes (Skrovankova et al, 2015;Saltan et al, 2016;Ersoy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%